1997
DOI: 10.1097/00007632-199707010-00005
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Lumbar Destabilization

Abstract: The unstable lumbar spine can be partially stabilized using fixation. Interbody bone provides additional stability. The immediate stability provided by pedicle screws is greater in lumbar vertebrae with higher bone density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…The vast majority of the studies on spinal arthropathy and disc degeneration suggest that increased mineral density of spinal and appendicular bones plays a role in etiopathogenesis (13)(14)(15)(16)(17). On the contrary, a few studies demonstrated that low spinal BMD is associated with degenerative changes in the lumbar spine (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of the studies on spinal arthropathy and disc degeneration suggest that increased mineral density of spinal and appendicular bones plays a role in etiopathogenesis (13)(14)(15)(16)(17). On the contrary, a few studies demonstrated that low spinal BMD is associated with degenerative changes in the lumbar spine (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…However, this is a too aggressive surgical practice for patients who generally have frequent association of other pathologies. Furthermore, when these transpedicular screws are inserted in less mineralized bones, the fixation is not as good as when they are placed in a normally mineralized bone (3) . A new technique was described (15) (6,11,21) .…”
Section: Spine Fracture Associated To Osteoporosis Is Found In 16% Ofmentioning
confidence: 99%
“…No entanto, esta é uma prática cirúrgi-ca muito agressiva para o paciente que, de um modo geral, freqüen-temente possui outras afecções associadas. Além disso, quando os parafusos transpediculares são inseridos num osso com menor massa óssea, não acontece a mesma fixação que ocorre quando são postos em um osso com densidade mineral normal (3) . Descreveram (15) uma nova técnica para estabilizar a coluna vertebral e que seja capaz também de melhorar a dor em pacientes portadores de hemangioma e tumores líticos metastáticos que acometiam essa região.…”
Section: Who Proposed the Use Of An Experimental Study Model In Compuunclassified
“…There are many factors that can lead to degradation of pedicle screw fixation (LaGrone et al 1988;Esses et al 1993;Heggeness et al 1993;Halvorson et al 1994;Kumano et al 1994;Pfeifer et al 1994;Chapman et al 1996;Kwok et al 1996;Polly et al 1998;Okuyama et al 2000;Polikeit et al 2003). Pedicle screws have been shown to loosen under certain conditions in patients with compromised bone strength (Coe et al 1990;Soshi et al 1991;Yamagata et al 1992;Okuyama et al 1993;Halvorson et al 1994;Bennett et al 1997;Hirano et al 1997;Wuisman et al 2000). Loosening represents failure at the bone -screw interface and is the most common mode of fixation failure when using modern implants.…”
Section: Introductionmentioning
confidence: 99%
“…Such alterations to traditional pedicle screw fixation generally yield increased resistance to pullout and/or 'windshield wiper' failure in the cephalad -caudad direction as reported in numerous studies (Zindrick et al 1986;Coe et al 1990;Soshi et al 1991;Yamagata et al 1992;Okuyama et al 1993;Halvorson et al 1994;Bennett et al 1997;Hirano et al 1997;Wuisman et al 2000;Cook et al 2001Cook et al , 2004Yazu et al 2005); however, there are inherent drawbacks and potential morbidities associated with these strategies. Although readily available in most operating rooms, polymethyl methacrylate cement is exothermic and can elicit a foreign body response (Yerby et al 1998;Renner et al 2001;Hasegawa et al 2005;Yazu et al 2005).…”
Section: Introductionmentioning
confidence: 99%